Springboard diving technical development features kinematical simulation research based on differential equation model - Peng, X.; Zeng, H. (BioTechnology: An Indian Journal, 2014)
Springboard diving is favored by broad masses due to its elegant movements, is one of most popular Olympic Games events. In recent years, with diving development, athletes.competitions has grown fiercely, scientific training way is the basis that ensure athlete get excellent results. The paper targeted springboard diving technical movements, combines with differential equation knowledge and kinematics, mechanics of materials as well as other knowledge, it makes force analysis of athletes and pedal, establishes differential equation model, and combines with computer analogue simulation technique, it tests on model and knows that model has practicability. Finally it inputs athletes kinematic parameters into differential equationmodel; solve differential equationmodel by computer technology, it gets calculation data results, so that analyzes data and makes improvement suggestions on springboard diving training with an aim to promote Chinese diving development. Abstract by Trade Science Inc. - INDIA